Institutions and democracy in Africa how the rules of the game shape political developments - Edited by Nic Cheeseman (New York Cambridge University Press, 2017)
Historically, African political institutions such as constitutions, legislatures and judiciaries have been seen as weak and vulnerable to manipulation, leading some to claim that the continent is 'institutionless'. However, recent developments including the consolidation of presidential term limits in a number of countries demonstrate that this depiction is no longer tenable. By drawing attention to how institutions can shape the practice of politics, this book demonstrates that electoral commissions, economic regulations and systems of land tenure are vital to our understanding of contemporary Africa. A series of cutting-edge contributions from leading scholars explain how the rules of the game shape political developments across the continent, from Kenya to Nigeria and from Benin to South Africa. In chapters that cover bureaucracies, constitutions, elections, political parties, the police and more, the authors argue that a new research agenda is required if we are to better understand the process of democratisation.
Includes bibliographical references and index.
Keywords: Political culture--Africa.